(untitled) (Journal of Educational Sciences, 2020)
The article deals with the application of synergetics in various sciences, including Biology. Synergy plays an important role in ensuring the development of the individual as a biological and intellectual subject. Synergetics helps to understand the processes of self-organization of human activity, the ordering of his actions. Properties considered in synergetics-autonomy and self-regulation allows us to draw certain parallels between cybernetic laws and the laws of synergetics. The synergetic approach, its ideas and main strategies can help autonomy, self-education of the individual, development of personal qualities. Conducting classes in Biology using synergetic methods is characterized by a variety of methods and their diversity, in contrast to traditional training and conducting classes. The authors are currently using the synergetic method when conducting several classes in Biology. In addition, synergetics has recently become one of the new interdisciplinary research areas in science that are of interest to the educational and scientific community around the world. It is provided an example in the article and summarizes the innovative experience of conducting Biology classes using a synergetic approach on the basis of gymnasium No. 176 in Almaty for 8th grade students. The content of the classes included integrated sections of the renewed Biology program. Key words: synergetics, pedagogy, natural sciences, educational process, traditional approach.